Analysis Of Investment Strategy For Adopting Battery Electric Vehicle Trucks in Indonesia (Case Study Of PT XYZ) - Rio Sadewo, Gregorious; Saragih Siallagan, Manahan Parlindungan (Jurnal Improsci, 2025)
Background. Indonesia's commitment to reducing greenhouse gas emissions through national policies and international agreements encourages the adoption of battery-electric vehicles. PT XYZ, a logistics company that operates more than a hundred diesel-powered trucks, is faced with a strategic decision regarding transitioning from internal combustion engine trucks to battery-based electric trucks amid changing technology and infrastructure readiness. Aims. This study aims to analyze PT XYZ's investment strategy for adopting electric battery-based trucks by identifying and prioritizing factors that influence the decision-making process. Methods. Using the Analytic Hierarchy Process (AHP) method as the main approach, this study evaluates technical, economic, infrastructural, environmental, social, governance, and corporate factors through a structured paired comparison. Result. The study's results show that economic, infrastructure, and governance factors are the most dominant considerations, and cost efficiency, availability of charging stations, and regulatory policies are the main drivers in decision-making. Conclusion. Based on the analysis's results, it was concluded that PT XYZ's adoption of electric battery-based trucks is not yet the optimal choice under current conditions, so maintaining a fleet of internal combustion engine trucks remains the most appropriate strategy. Implementation. This research provides valuable insights for PT XYZ and similar companies in emerging markets. It emphasizes the importance of aligning business strategy, infrastructure readiness, and regulatory support before adopting new vehicle technologies